Norway : 2007 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Norway. (IMF Staff Country Reports; Country Report, 2007)
This 2007 Article IV Consultation highlights that the Norwegian economy is set to grow strongly in 2007 for the fourth consecutive year. This economic performance is underpinned by strong monetary and fiscal policy frameworks. External demand, both for petroleum products and other Norwegian exports, is strong. Rapid credit growth, rising house prices, and tight labor markets are supporting domestic demand. Unit labor cost increases and core inflation have been subdued, although rapidly rising employment and increasing reports of labor shortages and wage drift indicate intensifying pressures.